2020
DOI: 10.1080/07391102.2020.1784289
|View full text |Cite
|
Sign up to set email alerts
|

In-silicoinvestigation of phytochemicals fromAsparagus racemosusas plausible antiviral agent in COVID-19

Abstract: COVID-19 has ravaged the world and is the greatest of pandemics in human history, in the absence of treatment or vaccine the mortality and morbidity rates are very high. The present investigation was undertaken to screen and identify the potent leads from the Indian Ayurvedic herb, Asparagus racemosus (Willd.) against SARS-CoV-2 using molecular docking and dynamics studies. The docking analysis was performed on the Glide module of Schr€ odinger suite on two different proteins from SARS-CoV-2 viz. NSP15 Endorib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 51 publications
1
58
0
1
Order By: Relevance
“…Similarly, Tyr495 and Tyr505 of the ACE2 binding region were involved with hydrogen bonding with the phytochemicals in the case of spike protein. These residues were also reported to be critical in binding to the ACE2 receptor (Chikhale et al, 2020). It can also be mentioned here that the therapeutic benefit of the phytochemicals is not limited to targeting spike and the main protease of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, Tyr495 and Tyr505 of the ACE2 binding region were involved with hydrogen bonding with the phytochemicals in the case of spike protein. These residues were also reported to be critical in binding to the ACE2 receptor (Chikhale et al, 2020). It can also be mentioned here that the therapeutic benefit of the phytochemicals is not limited to targeting spike and the main protease of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 71%
“…A pragmatic Ayurvedic treatment protocol for management of COVID-19 has also been proposed in a research publication [ 16 ]. Moreover, in silico studies have indicated that many herbs used in Ayurveda could have the abiliity to prevent cell entry of the SARS-CoV-2 virus [ 17 , 18 ]. While there is no conclusive evidence yet of the efficacy of specific Ayurvedic herbs, formulations or treatment protocols for COVID-19, it appears quite reasonable and plausible that Ayurveda can provide supportive care for patients diagnosed with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The screening of antiviral drugs has a certain reference significance. 20 , 21 The pathogenesis and complement activation pathways of novel coronavirus pneumonia are shown in Figure 2 .…”
Section: Potential Protein Targets In a Pandemicmentioning
confidence: 99%